2008
DOI: 10.1158/1078-0432.ccr-07-4433
|View full text |Cite
|
Sign up to set email alerts
|

HLA Class I Antigen Processing Machinery Component Expression and Intratumoral T-Cell Infiltrate as Independent Prognostic Markers in Ovarian Carcinoma

Abstract: Purpose: Defects in the antigen processing machinery (APM) may provide tumor cells with a mechanism to escape immune recognition. The purpose of this study is to determine the clinical significance of APM component down-regulation and tumor-infiltratingTcells in ovarian carcinoma. Experimental Design: After institutional review board approval, tumor samples from 150 patients with invasive epithelial ovarian cancers were examined for TAP1,TAP2, tapasin, HLA class I heavy chain (HLA-HC), h 2 microglobulin, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 32 publications
14
116
2
2
Order By: Relevance
“…[19][20][21]24 A former study has demonstrated that restoring tapasin gene expression in a mouse tumor model using viral vector transduction improved survival of model mice bearing lung carcinoma. 28 In this study, we generated human lung and colon cancer variants that express TAAs, survivin, or cep55, genetically lacking tapasin protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21]24 A former study has demonstrated that restoring tapasin gene expression in a mouse tumor model using viral vector transduction improved survival of model mice bearing lung carcinoma. 28 In this study, we generated human lung and colon cancer variants that express TAAs, survivin, or cep55, genetically lacking tapasin protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18] Notably, tapasin expression associated with intratumoral T-cell infiltration has been reported as a prognostic marker of patient survival in ovarian carcinoma, HNSCC, glioblastoma, and colorectal carcinoma. 12,13,[19][20][21] It is also reported that loss of tapasin is more frequent among the other antigen-processing machinery (APM) components, strongly suggesting its central role in escape from CTL immune surveillance to tumors. 15,22 Impaired CTL responses against tapasin-deficient cells have been well established in mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…6 Han et al immunostained components of the antigen-processing machinery (APM), including TAP1, TAP2, tapasin, HLA class I (HC-10), b2-microglobulin, CD3 C T cells, and CD8 C T cells. 7 They reported that APM component downregulation, lack of intratumoral T-cell infiltrates, and suboptimal cytoreduction were independent prognostic factors in multivariate analysis. In all previous studies, only the HLA class I heavy-chain staining using HC-10 was not an independent prognostic marker of ovarian cancer.…”
Section: Hla Class I Expression Is a Predictor Of Clinical Outcome Inmentioning
confidence: 99%
“…16,17 Tumors from women with high-grade serous cancers frequently show a host immune response, and the presence of cytotoxic T lymphocytes, and T-regulatory cells is consistently associated with favorable prognosis. [18][19][20][21][22][23][24] Germline mutations in BRCA1 and BRCA2 are present in B18% of ovarian cancer patients with high-grade serous carcinoma. [25][26][27] When combined with BRCA deficiencies that result from somatic mutations or epigenetic silencing, it appears that up to half of all high-grade serous ovarian cancers (hereditary and sporadic) have BRCA dysfunction.…”
mentioning
confidence: 99%